2009
DOI: 10.1177/1359104508100882
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Female Adolescents: An IPA Analysis

Abstract: Six female adolescents participated in open-ended interviews regarding their experiences of depression. The transcripts of their interviews were explored using Interpretative Phenomenological Analysis (Smith, 1991). The analysis revealed three inter-connected super-ordinate themes which were: communication, hurt self, and difference. These themes centred on communication processes in participants' families and with peers, issues relating to shifts in identity through adolescence, and feelings of being damaged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It is linked with chronic and severe forms of depression and concurrent and long-term negative psychosocial consequences, including educational underachievement and unemployment (Fergusson and Woodward 2002;Glied and Pine 2002;Zisook et al 2007). Personal accounts from young people highlight that depression is associated with significant distress and impacts negatively on social interactions, communication, and sense of identity (Midgley et al 2015;Shaw et al 2009).…”
mentioning
confidence: 99%
“…It is linked with chronic and severe forms of depression and concurrent and long-term negative psychosocial consequences, including educational underachievement and unemployment (Fergusson and Woodward 2002;Glied and Pine 2002;Zisook et al 2007). Personal accounts from young people highlight that depression is associated with significant distress and impacts negatively on social interactions, communication, and sense of identity (Midgley et al 2015;Shaw et al 2009).…”
mentioning
confidence: 99%
“…This separation could represent a loss of control or could re ect a protective act, preserving a primary construction of oneself as happy and rational, rather than de ned by more challenging thoughts and feelings and the actions they lead to. Indeed, research has identi ed instances of young people who over time have come to see symptoms and disorders as a central component of their identity, perhaps to hold onto a sense of stability for those experiencing turbulence in adolescence (23,58). From a therapeutic perspective, Midgley et al (18) have suggested that empowering young people to explore the meaning of their experiences and symptoms may offer greater feelings of control and order and, in turn, help them in re-establishing a sense of identity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been modest qualitative exploration of the ways adolescents that experience and understand mental health, including emotional symptoms. Some studies have examined subjective depression experiences, offering insight into how such di culties are perceived (18)(19)(20)(21)(22)(23)(24). This includes, for instance, indications that adolescents have different ways of conceptualising the variety of symptoms under the umbrella term "depression" (19,22), that they may experience bewilderment in understanding where di culties come from (18,19,21,22,24), and that depression can create identity shifts (18,20,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a method of analysis which has been used previously for mental health research, for instance, Macdonald, Sinason, and Hollins (2003) investigated participants with learning disabilities' experiences of group analytic therapy, and Newton, Larkin, Melhuish, and Wykes (2007) explored peoples' experiences of group therapy for auditory hallucinations. IPA has also been used to explore phenomena associated with depression and participants' feelings towards, and perceptions of the self (Shaw, Dallos, & Shoebridge, 2009;Smith & Rhodes, 2015).…”
Section: Interpretative Phenomenological Analysismentioning
confidence: 99%